Modulating salience network connectivity through olfactory nerve stimulation - Carina Heller; Maria Geisler; Nicolas L. Mayer; Annabelle Thierfelder; Martin Walter; Thomas Hummel; Ilona Croy (Translational Psychiatry)
Abstract Depression is associated with reduced functional connectivity within the brain’s salience network and its strengthened interactions with the default mode network (DMN). Modification of this clinical pattern is challenging. Leveraging the direct neural pathways from olfactory processing regions to the salience network, we explored the effects of electrical stimulation of the olfactory mucosa on brain connectivity. In a randomized, blinded within-subject design, 45 healthy individuals received olfactory or trigeminal nerve stimulation followed by resting-state fMRI. Olfactory stimulation resulted in a significant increase in functional connectivity between the salience network and the piriform cortex – a primary olfactory structure. Importantly, this stimulation increased functional connectivity within the salience network and weakened connectivity between the salience network and the DMN. These findings suggest that olfactory stimulation may modulate connectivity patterns implicated in depression, offering a novel potential minimal invasive therapeutic strategy. However, as these results were obtained from a healthy cohort, further studies are required to evaluate the efficacy in individuals with depression.